Industrial movements in Greek industry: Intragenerational trends - Kassimati, Koula (The Greek Review of Social Research, 1977)
This paper presents intragenerational trends in industrial mobility rates of employees in Greek industry and analyses variations of rates by means of individual’s socioeconomic features and characteristics of their social and industrial environment particularly. Intragenerational mobility is restricted to inter industrial movements and in this context the following will be studied: (i) job changes during respondent’s life, (ii) intragenerational occupational mobility during the period 1965-1974 and (iii) reasons motivating respondents to change or stay in the same job. To achieve these aims a sample of one thousand industrial workers employed in one hundred establishments of the Greater Athens area were extensively interviewed. The sampling design was based on the principles of two stage random sample (with the self weighing estimator).